'Supportive', 'real', and 'low-cost': implicit comparisons and universal assumptions in the construction of the prospective college-based HE student. Issue 8 (17th November 2018) - Henderson, Holly
Abstract: This paper first argues for the importance of continued analysis of marketising discourses in Higher Education (HE), both despite and because of their ubiquity. Secondly, the paper looks specifically at college-based HE provision in English Further Education (FE). Using the 'possible selves' concept alongside critical discourse analysis, the paper analyses the representations of prospective students on marketing web pages for HE provision in FE colleges. Arguing that the web pages reveal more than just the limited language of HE marketing strategy, the paper highlights common representations of the college-based HE student across policy, research and marketing sources. By exploring both the celebratory and the limiting nature of these representations, the paper therefore asks what the pages' projections of future or prospective students can tell us about current understandings of English college-based HE.